Implicit Religious Assumptions within the Resurgence of Civil Religion in the USA since 9/11 - Swatos, Jr, William H. (Implicit Religion, 2007)
Any number of societal reactions to the attacks of 11 September 2001 could be conceived as theoretical possibilities within the United States. In this article I want to make the argument that what a number of writers, but most notably Robert Bellah, have identified as civil religion in America provided the principal cultural resource that served to reintegrate and unite Americans in a coherent national response to the crisis. This is true because civil religion already existed as a cultural substratum and because it was, in fact, aspects of this very substratum that were under attack in the particular dynamics of these events. The thesis I propose is not a restudy of the civil religion concept qua concept. A variety of such studies have appeared from the 1970s to the 1990s and can be easily consulted by those interested in issues of conceptual development, refinement, elaboration, critique, and so on. I want to take the concept as broadly defined by Bellah, and empirically specified by Ronald Wimberley and colleagues in a series of subsequent investigations, and apply it to understanding the nature, function, and possible outcomes of the American response.